Quantitative detection of oxidative burst upon activation of plant receptor kinases - Albert, Markus; Fürst, Ursula (Plant Receptor Kinases, 2017)
The oxidative burst or the production of reactive oxygen species (ROS) is a typical cellular response of both plants and animals to diverse abiotic and biotic stresses. Mainly, the (re-)active oxygen species include the superoxide anion (O2−), hydrogen peroxide (H2O2), and the hydroxyl radical (OH•). Here, we outline the detection of extracellularly produced ROS in plant leaf pieces using a chemiluminescence-based bioassay with the luminol L-012 as a substrate being oxidized in the presence of ROS. Since this type of assay is in use in many laboratories, e.g., as a readout for activation of plant receptor kinases, we include a discussion on the interpretation of results and points addressing problems with the buffers at suboptimal pH values that negatively influence the chemiluminescence production.
CRIS-Team Scopus Importer:2020-03-09
Keywords: Biotic stress; Chemiluminescence; Hydrogen peroxide; Luminol; Oxidative burst; Plant development; Reactive oxygen species (ROS); Stress response; Superoxide anion